Desafíos, perspectivas y proyecciones del administrador educativo para el siglo XXI - María Eugenia Dengo-Obregón (Universidad Nacional, Costa Rica, 2001)
The author begins her essay outlining the desolating picture characterizing the human culture at the end of twentieth century. She discusses the steps backward that according to "The State of the Nation Report" Costa Rica has experienced as a nation in the educational field. In this context, she challenges educators, educational administrators and policy makers to exert their leadership to overcome this deteriorating trend. She stresses the urgency of a concerted process to develop and implement a ten-year educational improvement strategy. In regard to the period of time elapsing between modernity and post modernity, the author argues in favor of a new paradigm in the future that conciliates science, technique and spirituality within a new humanism.